Elevated carbon dioxide and ozone have weak, idiosyncratic effects on herbivorous forest insect abundance, species richness, and community composition. Issue 6 (26th May 2014) - Hillstrom, Michael L.; Couture, John J.; Lindroth, Richard L.
Abstract: Elevated concentrations of carbon dioxide and tropospheric ozone pose important threats to the abundance, diversity, and composition of forest arthropod communities. In turn, modification of arthropod communities may alter forest health, productivity, and ecosystem services. We studied the independent and interactive effects of elevated CO2 (eCO2 ) and elevated O3 (eO3 ) on the abundance, species richness, and community composition of herbivorous arthropods in stands of trembling aspen and paper birch at the Aspen Free Air CO2 Enrichment (FACE) site in northern Wisconsin, USA. We conducted timed, visual surveys of canopy arthropods during each of the summers of 2005, 2006, and 2007. We examined 26 983 arthropods on aspen and 8344 arthropods on birch across the fumigation treatments. Elevated CO2 and eO3 had species‐specific and temporally variable (i.e. idiosyncratic) effects on aspen and birch arthropod abundance and species richness. Weak, idiosyncratic effects of eCO2 and eO3 on herbivorous arthropod abundance and species richness did not significantly alter aspen arthropod community composition but occasionally altered birch insect community composition. Few interactive effects of CO2 and O3 were observed. Growing evidence suggests that the effects of eCO2 and eO3 on communities of insects are difficult to predict because responses are generally weak and species‐ and time‐specific. Although studies to date suggest that impacts of future atmospheres on insect community metrics are likely to be minimal, the possibility remains that effects on particularly important or susceptible species may cascade to alter trophic interactions and, ultimately, ecosystem processes.